Stability analysis of gravity anchorage: a case study of Taizhou Yangtze River Bridge. Issue 6 (1st April 2021) - Liu, Xu; Shao, Guojian; Huang, Jinsong; Su, Jingbo; Xu, Hongzhong
Abstract: This article presents a case study of the stability of the south anchorage of Taizhou Yangtze River Bridge in China. The gravity anchorage was embedded in soil and designed according to the current code of China. The code-based stability assessment is based on two-dimensional (2D) analyses under the assumption of plane strain conditions. Two typical failure modes of sliding and overturning are considered separately. The 2D plane strain model assumes the size of a structure in one dimension is significantly larger than the sizes in the other two dimensions. It is, thus, unsuitable for gravity anchorage because its sizes are similar in all three dimensions. Additionally, the effect of surrounding soil is ignored apart from the base friction in the anti-sliding stability assumption leading to the conservative design. Therefore, a three-dimensional model is more appropriate. Three-dimensional finite element model combined with strength reduction method is used to analyse the stability of anchorage. Reduced-scale model tests are used to calibrate the numerical model. The results show that the code-based design is indeed too conservative. The effects of stiffness and strength of the surrounding soil on the stability of anchorage are investigated through parametric studies to facilitate the economical design of gravity anchorage.